Evaluation of the Safety and Efficacy of Hydroxycitric Acid or Garcinia cambogia Extracts in Humans - Márquez, Fabiola; Babio, Nancy; Bulló, Mònica; Salas-Salvadó, J (Critical reviews in food science and nutrition, 2012)
Several studies have shown that Garcinia cambogia plays an important role in the regulation of endogenous lipid biosynthesis. This effect is specially attributed to (-)-hydroxycitric acid (HCA) inhibiting the enzyme ATP-dependent citrate lyase, which catalyzes the cleavage of citrate to oxaloacetate and acetyl-CoA. Although several studies have found that the administration of G. cambogia extracts is associated with body weight and fat loss in both experimental animals and humans, we should be cautious when interpreting the results as other randomized, placebo-controlled clinical trials have not reported the same outcomes. Furthermore, most studies in humans have been conducted on small samples and mainly in the short term. None of them have shown whether these effects persist beyond 12 weeks of intervention. Therefore, there is still little evidence to support the potential effectiveness and long-term benefits of G. cambogia extracts. With regard to toxicity and safety, it is important to note that except in rare cases, studies conducted in experimental animals have not reported increased mortality or significant toxicity. Furthermore, at the doses usually administered, no differences have been reported in terms of side effects or adverse events (those studied) in humans between individuals treated with G. cambogia and controls.